2002
DOI: 10.1046/j.0022-3042.2001.00721.x
|View full text |Cite
|
Sign up to set email alerts
|

Intraplantar injection of glutamate evokes peripheral adenosine release in the rat hind paw: involvement of peripheral ionotropic glutamate receptors and capsaicin‐sensitive sensory afferents

Abstract: Glutamate receptors have been identified on the peripheral terminals of both primary sensory afferents and sympathetic post-ganglionic neurons, and activation of these receptors produces peripheral sensitization and enhances nociception. Adenosine is an endogenous agent that has a regulatory effect on pain. In brain and spinal cord, adenosine release can be promoted by excitatory amino acids. In the present study, we used in vivo microdialysis to determine whether glutamate also can release adenosine in periph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(17 citation statements)
references
References 73 publications
0
17
0
Order By: Relevance
“…The authors suggested that ketamine reduces central hyperexcitability i. e. the site of action of ketamine was thought to be central. However recently, peripheral ionotropic [72] and metabotropic glutamate receptors [73] were found to be involved in nociceptive responses in animal experiments suggesting that a peripheral glutamate release might be involved in peripheral nociceptive mechanisms. In the biceps muscle glutamate levels remained elevated for about 2 h after injection of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…The authors suggested that ketamine reduces central hyperexcitability i. e. the site of action of ketamine was thought to be central. However recently, peripheral ionotropic [72] and metabotropic glutamate receptors [73] were found to be involved in nociceptive responses in animal experiments suggesting that a peripheral glutamate release might be involved in peripheral nociceptive mechanisms. In the biceps muscle glutamate levels remained elevated for about 2 h after injection of hypertonic saline.…”
Section: Discussionmentioning
confidence: 99%
“…There is a growing amount of experimental evidence showing that NMDA receptors are present in the periphery [34,35]. Furthermore, experimental studies indicate that peripherally administered NMDA receptor antagonists are effective in antinociception [36][37][38]. However, the role of the peripheral NMDA receptors in human pain is obscure.…”
Section: Variantsmentioning
confidence: 98%
“…The release of adenosine in response to injections of formalin or glutamate or to spinal nerve ligation has been studied (33)(34)(35)(36). glutamate administration evoked peripheral adenosine release in the rat hindpaw ( fig.…”
Section: Inflammatory Painmentioning
confidence: 99%
“…Adenosine may play a regulatory role in pain and inflammation in peripheral tissues (33). The release of adenosine in response to injections of formalin or glutamate or to spinal nerve ligation has been studied (33)(34)(35)(36).…”
Section: Inflammatory Painmentioning
confidence: 99%